2013
DOI: 10.1002/2013jd020978
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene emission variability through the twentieth century

Abstract: [1] A biochemical model of isoprene emission embedded within a global chemistry-climate simulation framework is applied to investigate the transient response to environmental change over the past century. In the model, the isoprene production is directly coupled to photosynthesis and depends on intercellular carbon dioxide concentration (CO 2 ), atmospheric CO 2 , and canopy temperature. Sensitivity runs are performed to isolate the relative roles of individual global change drivers: CO 2 , physical climate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 60 publications
7
30
0
Order By: Relevance
“…The trend analysis performed within this 527 study is in accordance with isoprene emission trends calculated by means of biochemical 528 emissions global models (Unger, 2013). However, the long term variability in isoprene could 529 be related to the climate oscillation.…”
Section: Isoprene 518supporting
confidence: 70%
“…The trend analysis performed within this 527 study is in accordance with isoprene emission trends calculated by means of biochemical 528 emissions global models (Unger, 2013). However, the long term variability in isoprene could 529 be related to the climate oscillation.…”
Section: Isoprene 518supporting
confidence: 70%
“…The larger reduction is comparable to results from previous studies that have estimated a 20-26 % reduction in biogenic VOC emissions from the late 19th century to the present day (Lathiere et al, 2010;Pacifico et al, 2012;Unger, 2013). Consistent with our study, Lathiere et al (2010) determined that the CO 2 sensitivity effect is the dominant driver of the change in isoprene emissions between 1901 and 2002, with the impact of land-use change about half that of CO 2 sensitivity.…”
Section: P Achakulwisut Et Al: Uncertainties In Isoprene Photochemisupporting
confidence: 87%
“…Consistent with our study, Lathiere et al (2010) determined that the CO 2 sensitivity effect is the dominant driver of the change in isoprene emissions between 1901 and 2002, with the impact of land-use change about half that of CO 2 sensitivity. In contrast, Pacifico et al (2012) and Unger (2013) found cropland expansion to be the dominant driver of the reduction. This discrepancy likely arises for two reasons.…”
Section: P Achakulwisut Et Al: Uncertainties In Isoprene Photochemimentioning
confidence: 81%
See 1 more Smart Citation
“…BVOCs are also important precursors for O 3 (Chameides et al, 1998) and secondary organic aerosol (SOA) formation (Kanakidou et al, 2005). Recent studies on historical emissions of BVOCs have shown that BVOC emissions have been affected by anthropogenic influences over the past millennium (Kaplan et al, 2011;Tanaka et al, 2012;Pacifico et al, 2012;Unger, Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%